2021
DOI: 10.1186/s40644-021-00417-3
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of renal angiomyolipoma without visible fat from small clear cell renal cell carcinoma by using specific region of interest on contrast-enhanced CT: a new combination of quantitative tools

Abstract: Background To investigate the value of using specific region of interest (ROI) on contrast-enhanced CT for differentiating renal angiomyolipoma without visible fat (AML.wovf) from small clear cell renal cell carcinoma (ccRCC). Methods Four-phase (pre-contrast phase [PCP], corticomedullary phase [CMP], nephrographic phase [NP], and excretory phase [EP]) contrast-enhanced CT images of AML.wovf (n = 31) and ccRCC (n = 74) confirmed by histopathology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The early dark cortical band sign can be observed in up to 60% of clear cell RCC cases, facilitating the differential diagnosis from fat-poor AML with high specificity and PPV[ 17 ]. Some studies demonstrate that the combination of quantitative data obtained by specific region of interest in corticomedullary phase[ 18 ], convention-radiomics CT nomogram[ 19 , 20 ], and circularity index on CECT[ 21 ] help distinguish fat-poor AML from clear cell RCC. Magnetic resonance parameters may be of value in evaluating RCCs[ 5 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The early dark cortical band sign can be observed in up to 60% of clear cell RCC cases, facilitating the differential diagnosis from fat-poor AML with high specificity and PPV[ 17 ]. Some studies demonstrate that the combination of quantitative data obtained by specific region of interest in corticomedullary phase[ 18 ], convention-radiomics CT nomogram[ 19 , 20 ], and circularity index on CECT[ 21 ] help distinguish fat-poor AML from clear cell RCC. Magnetic resonance parameters may be of value in evaluating RCCs[ 5 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, an S-ROI (area: 10-20 mm 2 ) and an M-ROI (area: 50-100 mm 2 ) were placed in the tumor regions exhibiting the greatest degree of enhancement in CMP images ( Figure 2 ). These 2 ROIs were placed with the following considerations: (i) S-ROI and M-ROI placement in PCP and NP images should be based on the positioning and sizing used for CMP images; (ii) regions of intratumoral vasculature, cystic degeneration, central scarring, and calcification should be avoided, with care being taken to differentiate between blood vessels and tumor-rich blood supply lesions based on previously defined morphological characteristics 10 ( Figure 2 ); and (iii) each parameter should be measured 2 times, with the average value being recorded as the attenuation value of the tumor (AVT). An additional ROI should then be placed within the adjacent renal cortical region to measure the attenuation value of the cortex (AVC), allowing for the lesion-to-cortex attenuation (L/C) ratio to be measured as follows: (AVT/AVC) × 100%.…”
Section: Methodsmentioning
confidence: 99%
“… 7 - 8 Rosenkrantz et al 9 found the use of a small ROI (S-ROI) to be more accurate than a large ROI (L-ROI) when differentiating between RCCs and cysts, with this approach being most effective when comparing pRCCs and cysts. Wang et al 10 also reported that S-ROI-based enhancement degree and whole ROI (W-ROI)-based enhancement heterogeneity were superior to medium ROI (M-ROI) when differentiating between small ccRCC and fat-poor angiomyolipoma (AML).…”
mentioning
confidence: 99%
“…The selection principles of the ROI were as follows [23], (Figure . 2). i) Contrast-enhanced CT was used to assess the edges and vessels of the mass for ROI measurements.…”
Section: Quantitative Ct Analysismentioning
confidence: 99%